Can the world afford autistic spectrum disorder? : nonverbal communication, asperger syndrome and the interbrain - Tantam, Digby (Jessica Kingsley Publishers, 2009)
"Digby Tantam argues in this book that the world affords us a web of subliminal nonverbal communication that regulates our brains. It helps us understand whether our beliefs do or do not have social approval, and it generally guides us in our relations with others. People with autism do not seem to be influenced by these subliminal signals and this results in the difficulties in social interaction that are so characteristic of all the autistic spectrum disorders. How is such nonverbal communication carried out, and why do people on the autism spectrum find it so difficult? What are the consequences of this for them, and how do these consequences affect their personality, self-awareness, and sense of place in the world? Digby Tantam explores the latest theories on nonverbal communication and how it shapes social behaviour. He provides abundant evidence for it being impaired in people with autism spectrum disorder (ASD). He shows how knowledge of this difference can be used to overcome some of the impairments in nonverbal communication in people with ASD, but also how acknowledging these problems can result in more positive development elsewhere. This groundbreaking book will be fascinating reading for anyone interested in communication, and particularly for people who have ASD themselves, for their families, and all professionals working with people on the autistic spectrum. It sharpens our understanding of the mysterious phenomenon of human communication and clarifies the special status of people with ASD, showing how much we can learn from their experience"--Provided by publisher.